eUtlibQual - Einasto, Olga (Qualitative and Quantitative Methods in Libraries, 2019)
The aim of this article is to present the instrument for the evaluation of e-service quality in academic library, based on the case study – service quality monitoring in the University of Tartu Library, Estonia. The article offers practical help to researchers and practitioners for e-service quality evaluating and improvement. The proposed approach allows gathering necessary information to focus strategic planning on services important for users and to efficiently allocate the library‟s resources.